Picturing worlds : visuality and visual sovereignty in contemporary Anishinaabe literature - Stirrup, David (American Indian studies series, 2020)
"Picturing Worlds examines the uses that a range of Anishinaabe authors make of art and artists. It examines the ways these authors establish frameworks for continuity, resistance, and sovereignty in that "space" where conventional narratives of settlement read rupture"--